2013
DOI: 10.5005/jp-journals-10005-1201
|View full text |Cite
|
Sign up to set email alerts
|

Cornelia De-Lange Syndrome: A Case Report

Abstract: Cornelia de-Lange syndrome is a congenital anomaly syndrome characterized by distinctive facial dysmorphism, primordial short stature, hirsutism, and upper limb reduction defects that range from subtle phalangeal abnormalities to oligodactyly. Craniofacial features include synophrys, arched eyebrows, long eyelashes, small widely spaced teeth and microcephaly. IQ ranges from between 30 and 102 with an average of 53. Many individuals demonstrate autistic and self-destructive tendencies. It is an autosomal domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…9 In this case, a 53-month-old boy was referred by the pediatrician with global or adactyly features. 10 In another case report, a CdLS patient was diagnosed without limb malformation criteria. 11 Cheng et al found that CdLS patients had small hands with small 5th fingers12.…”
Section: Case Discussionmentioning
confidence: 99%
“…9 In this case, a 53-month-old boy was referred by the pediatrician with global or adactyly features. 10 In another case report, a CdLS patient was diagnosed without limb malformation criteria. 11 Cheng et al found that CdLS patients had small hands with small 5th fingers12.…”
Section: Case Discussionmentioning
confidence: 99%
“…Autosomal dominant [22] -Cherubism -Mental deficiency Cornelia de Lange syndrome -Primordial growth deficiency -Facial dysmorphism -Distinct craniofacial features [23] Cross syndrome Autosomal Recessive -Hypopigmentation -Microphthalmia Gingival fibromatosis with Murray syndrome (Murray-Puretic-Drescher syndrome, juvenile hyaline fibromatosis) Mutations in capillary morphogenesis protein-2 (CMG-2 gene) Nodular, papular skin lesions Ambras syndrome -Extreme hypertrichosis involving the shoulders, face, nose, and ears [24] Rutherford syndrome -Delayed tooth eruption -Mental retardation -Aggressive behavior [25] Table 2: Syndromes associated with gingival bleeding Syndromes Genetics Shwachman-Diamond syndrome SBDS gene is located at chromosome 7q11 [26] Myelodysplastic syndrome (MDS) Hemorrhagic lupus anticoagulant syndrome Craniofacial arteriovenous metameric (CAMS) syndrome Epstein syndrome Mutations affecting the myosin heavy chain (MYH-9) gene [28] . Osler-Rendu-Weber Syndrome (Hereditary hemorrhagic telangiectasia) Asthenia-polyarthritis.…”
Section: Ramon Syndromementioning
confidence: 99%
“…Cornelia de-Lange syndrome (CdLS) was first described as a distinct syndrome in 1933, by Dr Cornelia de-Lange, a Dutch paediatrician, after whom the disorder has been named, though the first ever documented case was in1916 by Dr Brachmann. (1) It is a rare genetic disorder characterised by facial dysmorphia (arched eyebrows, synophrys, depressed nasal bridge, long philtrum, down-turned angles of the mouth), upper-extremity malformations, hirsutism, cardiac defects, growth and cognitive retardation, and gastrointestinal abnormalities. (2) Seizure is found about 20% of cases majority being partial seizure type (64.3 %).…”
Section: Introductionmentioning
confidence: 99%